2001
DOI: 10.1021/ie000505y
|View full text |Cite
|
Sign up to set email alerts
|

Pressure Effect on the Flow Fields and the Reynolds Stresses in a Bubble Column

Abstract: The hydrodynamics of bubble columns operated at pressures up to 7.0 MPa are investigated using a laser Doppler velocimetry system. Laser Doppler velocimetry is a noninvasive optical technique, which is used to conduct in situ measurements of velocity, with high spatial resolution, fast dynamic response, and the ability to detect flow. The axial and tangential velocities and the Reynolds shear and normal stresses are analyzed and discussed in relation to large-scale structures present in the flow. This study de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2002
2002
2008
2008

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 11 publications
1
9
0
Order By: Relevance
“…Therefore, the extent of liquid mixing is reduced at elevated pressures. Our recent study of flow fields and Reynolds stresses in high-pressure bubble columns using the laser Doppler velocimetry technique (Lee et al, 2001) also confirmed that the bubble-induced turbulence of the liquid phase is depressed as the pressure increases. The combined variations of liquid-phase turbulent fluctuations and internal liquid circulation give rise to the overall effect of pressure on liquid mixing.…”
Section: Effect Of System Pressuresupporting
confidence: 57%
“…Therefore, the extent of liquid mixing is reduced at elevated pressures. Our recent study of flow fields and Reynolds stresses in high-pressure bubble columns using the laser Doppler velocimetry technique (Lee et al, 2001) also confirmed that the bubble-induced turbulence of the liquid phase is depressed as the pressure increases. The combined variations of liquid-phase turbulent fluctuations and internal liquid circulation give rise to the overall effect of pressure on liquid mixing.…”
Section: Effect Of System Pressuresupporting
confidence: 57%
“…Reynolds normal and shear stresses at z/D ) 4 for the perforated plate sparger are shown in Figure 8. It can be seen that the normal stresses are much higher than the shear stresses as also observed by Lee et al 16 and Kulkarni et al 9 However, the axial-radial Reynolds shear stress (u′V′) is important to generate the liquid circulation in the column. 17,18 Hence, we have given the radial profiles for the same in Figure 9.…”
Section: K )mentioning
confidence: 69%
“…Reynolds normal and shear stresses at z / D = 4 for the perforated plate sparger are shown in Figure . It can be seen that the normal stresses are much higher than the shear stresses as also observed by Lee et al and Kulkarni et al However, the axial-radial Reynolds shear stress ( ) is important to generate the liquid circulation in the column. , Hence, we have given the radial profiles for the same in Figure . For the porous plate sparger, Reynolds shear stress is typically much small (except near the sparger), indicating that the circulation is not as strong as in case of perforated plate sparger.…”
Section: Resultsmentioning
confidence: 87%
“…Therefore, the extent of liquid mixing is reduced at elevated pressures. Our recent study of flow fields and Reynolds stresses in high-pressure bubble Ž columns using the laser Doppler velocimetry technique Lee . et al, 2001 also confirmed that the bubble-induced turbulence of the liquid phase is depressed as the pressure increases.…”
Section: Effect Of System Pressurementioning
confidence: 99%